Merdeka Curriculum as a Form of Pancasila Student Profile in Madrasah Ibtidaiyah - Akhmad Afnan Fajarudin (Journal of Islamic Education Research, 2023)
The term “Merdeka Curriculum” is being discussed by both educators and academics. The emergence of this curriculum is anxiety in itself because the education system in Indonesia changes when the Minister of Education changes. Presumably, the concept carried by each curriculum change also tends to be the same, namely adaptation to change. Conceptually, this article will discuss the profile of Pancasila students in strengthening character education in madrasas. The literature review approach is in the form of descriptive analysis. The data used in literature research comes from the text finding and discourse analysis. This research only uses literature sources as data without researchers coming to the field. The results showed that the concept of an independent curriculum in strengthening character education uses a project-based learning approach used in implementing P4 in madrasah. There are three stages in identifying madrasah readiness in determining project-based implementation readiness, namely initial, development, and advanced of  stage. Several stages of strategies can be adapted and developed in the madrasah environment, namely strengthening school culture or creating school culture and the implementation of school student profile projects carried out in intracurricular and extracurricular activities.